Estágio supervisionado: reflexões da observação e regência em uma turma do Ensino Médio na cidade de Castanhal - LOPES, Geiza das Mercês (2024)
This work aims to analyze and reflect on the constituent aspects of the Supervised Internship in Mathematics for teacher education. To this end, the qualitative approach plus the bibliographic research was used as a methodology to support the internship perspective and the relationships established in this process. In this sense, I analyze the final report of the discipline of Stage IV, in order to understand the process of the school-internship-university relationship, as well as the importance of the internship in the formation of the professional and teaching identity of the then undergraduate. As a result, we found that the Internship is essential for the construction of identity, professional posture and essential knowledge for teaching.